Anatoly Ivanovich Zhigun - "Orthopaedics, traumatology and prosthetics", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
The article is dedicated to Dr of Medical Sciences Anatoly Ivanovich Zhigun.